Autobiographical memory in suicide attempters. - Williams, J; Broadbent, K (1986)
Mood-memory phenomena have been studied using laboratory mood induction procedures with nondepressed subjects and with clinically depressed individuals. The present study examined both hedonic and nonhedonic aspects of autobiographical memory in people who had recently attempted suicide by overdose. Attempted suicide subjects, who were required to retrieve specific personal memories to positive or negative cue words, showed biased retrieval when their performance was compared with that of control groups, but the bias was wholly due to delayed retrieval of positive memories rather than speeded retrieval of negative memories. At least part of this effect was due to inappropriate retrieval strategies that yielded general rather than specific memories in the overdose group and have implications for associative network models of emotional memory. © 1986 American Psychological Association.